The Influence of Capital Structure and Dividend Payments on Corporate Income Tax Expenses Payable to Manufacturing Companies Listed on the IDX - Desmiwerita Desmiwerita; Amalina Maharani (DINASTI RESEARCH, 2023)
Manufacturing companies need capital for business expansion and are companies that require management in paying taxes owed to maximize profits. This research examines the influence of capital structure and dividend payments on the corporate income tax burden payable to manufacturing companies listed on the Indonesia Stock Exchange in 2010-2014. The method used in this research is purposive sampling and uses multiple linear regression. Data obtained from financial reports at manufacturing companies. The research results show that capital structure has a significant effect on the income tax burden payable, dividend payments do not have a significant effect on the income tax burden payable and capital structure and dividend payments together have a significant effect on the income tax burden payable.